The Palace of Minos at Knossos - Scarre, Christopher; Stefoff, Rebecca, 1951- (New York : Oxford University Press, 2003)
Discusses the ancient Minoan civilization of Knossos, Crete, as manifested by the excavations of that city by the archaeologist Sir Arthur Evans.
An unexplored world -- Discovering a lost palace -- In search of the Minoans -- Knossos today -- Inerview with Cris Scarre.
Includes bibliographical references (p. 44) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Evans, Arthur, -- Sir, -- 1851-1941 -- Juvenile literature; Evans, Arthur, -- Sir, -- 1851-1941.; Palace of Knossos (Knossos) -- Juvenile literature; Palace of Knossos (Knossos); Excavations (Archaeology) -- Greece -- Crete -- Juvenile literature; Excavations (Archaeology) -- Greece; Knossos (Extinct city) -- Juvenile literature; Crete (Greece) -- Antiquities -- Juvenile literature; Knossos (Extinct city); Crete (Greece) -- Antiquities; Electronic books